Characterizing the genotypic spectrum of retinitis pigmentosa in East Asian populations: a systematic review. (4th March 2023) - Lee, Brian Juin Hsien; Tham, Yih-Chung; Tan, Tien-En; Bylstra, Yasmin; Lim, Weng Khong; Jain, Kanika; Chan, Choi Mun; Mathur, Ranjana; Cheung, Chui Ming Gemmy; Fenner, Beau J.
ABSTRACT: Background: Ongoing trials for retinitis pigmentosa (RP) are genotype-specific, with most trials conducted on European cohorts. Due to genetic differences across diverse ancestries and populations, these therapies may not be efficacious in East Asians. Materials and Methods: A literature search was conducted from 1966 to September 2022 for cohort studies on East Asian populations reporting on non-syndromic RP genotypes and variants. Population-weighted prevalence was used to determine the genotypes and individual variants across the entire cohort. The carrier prevalence of common variants was compared against those in Europe. Results: A total of 12 articles describing 2, 932 clinically diagnosed East Asian RP probands were included. We identified 876 variants across 54 genes. The most common genotypes included USH2A, EYS, RPGR, ABCA4, PRPF31, RHO, RP1, RP2, PDE6B and SNRNP200, with USH2A as the most common (17.1%). Overall, 60.5% of probands with clinically relevant variants were found to have one of the genotypes above, with 543/876 (62.0%) of the variants occurring in these genes. The most frequently reported variant was USH2A missense variant c.2802T>G/p.C934W (4.9%). Carrier prevalence of these variants was significantly different ( p  < 0.0001) than in Europe. Conclusions: USH2A was the most commonly affected RP gene in this East Asian cohort, although sub-population analysis revealed distinct genotype prevalence patterns. While the genotypes are similar between East Asia and European cohorts, variants are specific to East Asia. The identification of several prevalent variants in USH2A and EYS provides an opportunity for the development of therapeutics that are relevant for East Asia patients.